Épistémologie et pédagogie chez Jean Piaget et Karl Popper - Alain Firode (Recherches en Éducation)
This paper aims at examining, from an educative point of view, the differences between Piaget’s genetic epistemology and Popper’s evolutionary epistemology. Both thinkers set out a theory of the mind according to which human knowledge appears as a consequence of biological adaptation. Nevertheless, Popper disagrees with Piaget about two important questions: 1) Popper’s theory rests on a neo-Darwinian framework which rejects the Piagetian idea of equilibrium between self and the world; 2) unlike Piaget, who considers human thought as a purely mental entity, Popper considers that a thought, once formulated in language, gains autonomous existence (it becomes an “object” outside the mind). Several important consequences, concerning theory of learning and theory of child cognitive development, ensue from these oppositions.